Combination romidepsin and azacitidine therapy is well tolerated and clinically active in adults with high-risk acute myeloid leukaemia ineligible for intensive chemotherapy - Loke, J; Metzner, M; Boucher, R; Jackson, A; Hopkins, L; Pavlu, J; Tholouli, E; Drummond, M; Peniket, A; Bishop, R; Fox, S; Vyas, P; et al. (British Society for Haematology, 2021)
Azacitidine (AZA) is important in the management of patients with acute myeloid leukaemia (AML) who are ineligible for intensive chemotherapy. Romidepsin (ROM) is a histone deacetylase inhibitor which synergises with AZA in vitro. The ROMAZA trial established the maximum tolerated dose (MTD) of combined ROM/AZA therapy in patients with AML, as ROM 12 mg/m2 on Days 8 and 15, with AZA 75 mg/m2 administered for 7/28 day cycle. Nine of the 38 (23·7%) patients treated at the MTD were classified as responders by Cycle 6 (best response: complete remission [CR]/incomplete CR n = 7, partial response n = 2). Correlative next-generation sequencing studies demonstrated important insights into therapy resistance.